Continuous countercurrent chromatographic twin‐column purification of oligonucleotides: The role of the displacement effect. Issue 7 (6th April 2022) - Fioretti, Ismaele; Müller‐Späth, Thomas; Weldon, Richard; Vogg, Sebastian; Morbidelli, Massimo; Sponchioni, Mattia
Abstract: Oligonucleotides (ONs) are breaking through in the biopharmaceutical industry as a promising class of biotherapeutics. The main success of these molecules is due to their peculiar way of acting in the cellular process, regulating the gene expression and hence influencing the protein synthesis at a pretranslational level. Although the Food and Drug Administration (FDA) already approved a few ON‐based therapeutics, their production cost strongly limits large‐scale manufacturing: a situation that can be alleviated through process intensification. In this study, we address this problem by developing an efficient and continuous chromatographic purification process for ONs. In particular, we considered the chromatographic purification of an ON crude prepared by chemical synthesis using anion exchange resins. We demonstrate that in this system the competitive adsorption of the various species on the same sites of the resin leads to the displacement of the more weakly adsorbing species by the more strongly adsorbing ones. This phenomenon affects the behavior of the chromatographic units and it has been investigated in detail. Then, we developed a continuous countercurrent solvent gradient purification (MCSGP) process, which can significantly improve the productivity and buffer consumption compared to a classical single‐column, batch chromatographic process. Abstract : The chromatographic purification of oligonucleotides is challenging and leads to discarding huge amounts of out‐of‐specification product co‐eluting with structurally similar impurities. Multicolumn Countercurrent Solvent Gradient Purification (MCSGP) can significantly improve the yield and productivity of the process when targeting at a given purity specification, lowering the environmental footprint of the process. In addition, the displacement of the weak impurities by the product can be advantageously exploited to further improve the process performances by increasing the loading.